Cardio‐Invasive Metastatic Squamous Cell Carcinoma of the Lung Masquerading as Acute ST Elevation Myocardial Infarction - Nihar Jena; Shreya Tiwary; Deepak Chandramohan; Sreekant Avula; Prashanth Reddy; Harkesh Arora; Geetha Krishnamoorthy; Kirit Patel; Aiden Abidov (Clinical Case Reports)
ABSTRACT The incidence of secondary cardiac malignancies is on the rise due to the aging population. A 63‐year‐old male presented with recurrent chest pain and anterior ST elevations on ECG, leading to primary PCI, but continued to experience chest pain and persistent ST elevation. Cardiac imaging revealed a cardio‐invasive lung malignancy.